Does retail image affect attitude and repatronage intention of apparel store in Malaysia? - Harun, Amran; Rashid, Umi Kartini; Chia, Tatilya Ching Mei; Mohd Kassim, Abdul Wahid; Tahajuddin, Sulaiman (WSEAS (World Scientific and Engineering Academic Society) TRANSACTIONS, 2018)
Local apparel retailers in Malaysia are facing hard times to compete with the international companies and foreign brands. Thus, it is very crucial to understand how store image would influence Malaysian consumers’ store selection especially for the apparel retailers. The aim of this study is to examine the relationships between the store image, consumers’ attitude towards store and their repatronage intentions. The store image is conceptualized as a six multidimensional variable namely store atmosphere, store value, salesperson, merchandising, availability and after sale service. The research instruments were distributed among 185 apparel shoppers of age 18 and above who have recently visited any of foreign or local apparel retail stores. Importantly, results indicated five store dimensions namely store atmosphere, availability, salesperson, after sale and merchandising have significant effects on both consumers’ attitude towards store and repatronage intentions. Hence, the findings of this study provide useful insights for local apparel retailers to identify the key store attributes that significantly affect local consumers’ attitude and repatronage intention.